2016
DOI: 10.15406/bbij.2016.03.00061
|View full text |Cite
|
Sign up to set email alerts
|

On Modeling of Lifetime Data Using One Parameter Akash, Lindley and Exponential Distributions

Abstract: Shanker 1 introduced a new distribution named, 'Akash distribution'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Similarly, at 1   , PLD reduces to Lindley distribution introduced by Lindley (1.11) Ghitany et al (2008) have a detailed study about various properties of Lindley distribution, estimation of parameter and application for modelling waiting time data from a bank and it has been shown that it gives better fit than exponential distribution. Shanker et al (2016) have a detailed and critical comparative study of modelling real lifetime data from engineering and biomedical sciences using Akash, Lindley and exponential distribution and observed that each of these oneparameter distribution has some advantage over the other but none is perfect for modelling all real lifetime data. Since Ishita distribution gives better fit than Akash, Lindley and exponential distribution, it is expected and hoped that the twoparameter power Ishita distribution (PID) will provide a better model over twoparameter power Akash distribution (PAD) and power Lindley distribution (PLD) and one-parameter Ishita, Akash, Lindley and exponential distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, at 1   , PLD reduces to Lindley distribution introduced by Lindley (1.11) Ghitany et al (2008) have a detailed study about various properties of Lindley distribution, estimation of parameter and application for modelling waiting time data from a bank and it has been shown that it gives better fit than exponential distribution. Shanker et al (2016) have a detailed and critical comparative study of modelling real lifetime data from engineering and biomedical sciences using Akash, Lindley and exponential distribution and observed that each of these oneparameter distribution has some advantage over the other but none is perfect for modelling all real lifetime data. Since Ishita distribution gives better fit than Akash, Lindley and exponential distribution, it is expected and hoped that the twoparameter power Ishita distribution (PID) will provide a better model over twoparameter power Akash distribution (PAD) and power Lindley distribution (PLD) and one-parameter Ishita, Akash, Lindley and exponential distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Shanker [2] has discussed its mathematical and statistical properties including its shape, moments, skewness, kurtosis, hazard rate function, mean residual life function, stochastic orderings, mean deviations, distribution of order statistics, Bonferroni and Lorenz curves, Renyi entropy measure, stress-strength reliability, amongst others along with the estimation of parameter and applications for modeling lifetime data from engineering and biomedical science. Shanker et al [3] has detailed and critical study about the applications of one parameter Akash, Lindley and exponential distributions for modeling lifetime data from biomedical science and engineering. about origin and the variance has been presented.…”
Section: Introductionmentioning
confidence: 99%
“…While searching a lifetime distribution which gives better fit than exponential and Lindley, Shanker 1 has introduced a lifetime distribution named Akash distribution and showed that Akash distribution gives much better fit than both exponential and Lindley distributions. Shanker et al, 4 have comparative study on the modeling of lifetime data using Akash, Lindley and exponential distribution and observed that there are several situations where these lifetime distributions are not suitable either from theoretical or applied point of view. Therefore, an attempt has been made in this paper to obtain a new lifetime distribution which is flexible than Akash, Lindley and exponential distributions for modeling lifetime data in reliability and in terms of its hazard rate shapes.…”
Section: Introductionmentioning
confidence: 99%